(untitled) (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
This study examines the implementation of inclusive Islamic Religious Education (PAI) at SMPIT Al Uswah Bangil, focusing on strategies that integrate students with special needs into regular classrooms. The research highlights the school’s adaptive approach, combining modified lesson plans, flexible teaching methods (lectures, Q&A, demonstrations, and technology), and strategic classroom management to ensure equitable learning. Key findings reveal that personalized instruction, peer collaboration, and supportive teacher-student relationships enhance participation and comprehension for all learners. While assessments follow the standard curriculum, accommodations are made to address diverse abilities. The study also underscores the effectiveness of faith-based interventions, such as Quranic therapy and reward-penalty systems, in supporting students with special needs. Ultimately, the findings advocate for stronger institutional commitment to inclusive education, backed by parental involvement and policy reforms, affirming education as a universal right that must cater to every learner’s unique potential.